Hubungan Pemberian Makanan Pendamping ASI Pada Bayi Usia 6-24 Bulan Dengan Kejadian Obstipasi - Retno Dewi Prisusanti; Nur Zad Malikha1 (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Obstipation is defined as the absence of fecal expenditure for 3 days or more. To prevent the baby from experiencing obstipation disorders, parents should consider the timing of delivery, shape, frequency, type, amount of food, and how to make according to age 6-24 months. The purpose of this study to determine the relationship of giving of breast milk in infants aged 6-24 months with the incidence of obstipation in Posyandu Melati Kepuh Village Kertosono District Nganjuk Year 2017. This research is an analytical research that is cross sectional. Sample of 37 respondents. Data collection using questionnaires. To know the existence of the relationship used statistical test Chi-Square. Chi-Square statistical test results with α = 0.05 obtained Exact Sig. (2-sided) (p) is 0.005 thus p